Contracted chattel : indentured and apprenticed labor in Cape Town, c.1808-1840 - Iannini, Craig; Iannini, Craig (Department of Historical Studies, 2017)
This thesis examines indentured and apprenticed labor in Cape Town between the years 1808 and 1840. Through analysis of primary material such as the South African Commercial Advertiser, the Colonist, and the Mediator, as well as contemporary travel accounts, contracts of indenture and apprenticeship, and an examination of the records of the Cape Town Magistrates, this study explores the attitudes and perceptions towards indentured and apprenticed labor by both employers and indentured and apprenticed servants.This study hopes to add to the existing literature pertaining to nineteenth-century Cape Colony labor. This thesis commences with an examination of the different indenture and apprenticeship systems which existed in Cape Town between the years 1808 and 1840. It explores the issue of how employers and the government sought to maintain a constant supply of labor in the city as the prominence of urban slavery declined. It also discusses the important issue of how employers defined the terms apprentice and indenture. Chapter two explores the topic of child apprenticeship in Cape Town between the years 1812 to 1840, and illustrates that the notion of child apprenticeship was understood in different ways between employers and parents of apprenticed children. Chapter three investigates the stereotypes Cape Town's English speaking employers held towards the city's indentured and apprenticed laborers. The final chapter explores the question of status and incorporation into Cape Town society for the city's indentured and apprenticed laborers, and demonstrates that laborers did not enjoy equal status to the city's slaves.